Neuropsychiatric abnormalities in familial frontotemporal dementia: Findings from the LEFFTDS Cohort: Neuropsychiatry and behavioral neurology: Neuropsychiatric symptoms in MCI and dementia. (7th December 2020) - Forsberg, Leah K.; Boeve, Bradley F.; Rosen, Howard J.; Boxer, Adam L.; Syrjanen, Jeremy; Brushaber, Danielle; Coppolla, Giovanni; Dickerson, Brad C.; Fields, Julie A.; Fong, Jamie; Gavrilova, Ralitza H.; Ghoshal, Nupur; et al.
Abstract: Background: The LEFFTDS Consortium involves investigators at 8 centers in North America evaluating individuals in kindreds with mutations in microtubule associated protein tau ( MAPT ), progranulin ( GRN ), or chromosome 9 open reading frame 72 ( C9orf72 ) genes using a standardized battery of measures. Participants are evaluated annually. We sought to determine possible correlations between FTLD disease progression and neuropsychiatric features. Method: The Neuropsychiatric Inventory Questionnaire (NPI‐Q) scale is an informant‐based instrument that measures the presence and severity of 12 neuropsychiatric features in patients with dementia. The NPI‐Q was completed at each LEFFTDS visit. The individual NPI questions and total score were analyzed in those with CDR® Dementia Staging Instrument PLUS National Alzheimer Coordinating Center Frontotemporal Lobar Degeneration (CDR®+ NACC FTLD) ratings of 0 (i.e., clinically normal), 0.5 (i.e., questionably/minimally abnormal), 1, 2, and 3. Result: The 472 participants enrolled to date with a baseline (Visit 1) assessment have the following characteristics: 261 (55.5%) female, mean age 48 (range 18‐80) years, mean education 16 (range 11‐22) years, and 275 participants with a CDR®+NACC FTLD=0 (58%) and known genetic status. Participants with a CDR®+NACC FTLD=0 plus a genetic mutation were compared to those without a mutation and found to have increased severity of apathy (mean score of 0.116 versus 0.035, p=0.0302). Regardless of the specific mutation, those with a CDR®+NACC FTLD=0.5 were reported to have increased severity of apathy, disinhibition, and irritability. For most domains, mean NPI‐Q severity scores increase between groups up to CDR®+NACC FTLD=2. Depression increases in severity up to CDR®+NACC FTLD=1, whereas apathy severity continues to increase with increasing disease severity through CDR®+NACC FTLD=3. Twenty participants converted from CDR®+NACC FTLD 0 to >0 between their baseline and most recent visit; apathy severity almost tripled in these participants. For those that converted, disinhibition, irritability, and NPI total score were different between baseline and most recent visit (Wilcoxon signed rank test, p<0.05). Conclusion: Key neuropsychiatric features measured by the NPI‐Q demonstrate differences in apathy severity between clinically normal mutation vs non‐mutation carriers. Key domains differ at different levels of FTLD severity and show dynamic changes with increasing level of FTLD severity. Supported by AG063911, AG045390, NS092089, AG016976.